PEMBELAJARAN KETERAMPILAN BERBICARA TEMA “MEMBUAT NASI GORENG” DENGAN MENGGUNAKAN METODE COOKING CLASS PADA MAHASISWA PROGRAM BIPA DARMASISWA UNISSULA TAHUN AKADEMIK 2019/2020 - Evi Chamalah, Aida Azizah, dan Oktarina Puspita Wardani, Meilan Arsanti, (Sasando, 2020)
Speaking Skill learning is one of cumpolsory courses for students in Darmasiswa Program. This study aimed to describe Speaking Skill learning through cooking class method for students of BIPA level B1, Darmasiswa Program, Sultan Agung Islamic University, 2019/2020. Method used in this study was qualitative descriptive method. This study obtained sources from informants, documents, and notes in observation result. This study conducted observation, interview and document analysis in order to collect data. The data validity was tested by method triangulation, data source triangulation, and informant reviews. Data analysis technique used in this study was interactive analysis technique. Based on the result of assessment on speaking skill, it was obtained that respondent 1 got score of 89 in Perfect category (A), respomdent 2 got 84 in Very Satisfying category (AB), and respondent 3 got 79 in Very Satisfying category (AB). Furthermore, it could be concluded that the usage of cooking class method was helpful and able to facilitate the students in Speaking Skill learning on theme of 'Cooking Anticovid-19 Fried Rice' using Indonesian Language well and fluently. In addition, the students got more interest and motivation to participate in Speaking Skill class.